(untitled) (Bangladesh Journal of Microbiology, 2018)
Seven florally diversified Bangladeshi honey samples were assessed for their physicochemical properties as well as their antibiogram profile on different human pathogenic bacterial strains. The average density, total protein content, ascorbic acid content, total phenolics content and the total antioxidant capacity of these honeys were determined as 1.50±0.09 g/ml, 5.63±1.56 mg/g, 91.87±22.16 mg/g, 571.04±289.02 mg gallic acid equivalent/gram, and 320.74±55.06 mg ascorbic acid equivalent/gram of samples, respectively. A significant correlation between the phenolics content and the total antioxidant capacity was observed in commercially available honey samples. However, the natural honey samples showed the best antibacterial activity against different pathogenic multidrug-resistant bacterial strains. Significant antibacterial activities were observed against Klebsiella pneumoniae, Salmonella typhi, Micrococcus luteus, Pseudomonas spp. and Enterobacter spp. and moderate antibacterial activities was observed on Shigella boydii, Bacillus cereus, Bacillus megaterium, and Bacillus subtilis. The antibacterial activity was correlated with the total antioxidant capacity. This study suggested that the Bangladeshi multifloral honeys have clinical potential against multidrug-resistant pathogenic bacterial strains. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 5-9